EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN DURIAN (DURIO ZIBETHINUS MURR) DI KECAMATAN 2X11 KAYUTANAM KABUPATEN PADANG PARIAMAN - edgar, nurul rahmadilla (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
ABSTRACT This study aims to determine the suitability of land for durian plants and to find out how much the productivity of durian plantations in 2x11 Kayutanam District, Padang Pariaman Regency. The type of research used is descriptive quantitative. The data analysis method used is the overlay method between soil maps, slope maps, geological maps, landform maps. Data collection techniques in the form of field observations, interview, and laboratory analysis. The dat analysis technique is to determine the land suitability class by matching between the growing requirements of durian plants with the characteristics of the land. The results in this study are (1) the research area has 2 categories of land suitability classes, namely suitable (S1) with an area of 15116 Ha or 74.62% and quite appropriate class (S2) with an area of 5139 Ha or 25.37%. (2) the productivity of durian plants in the very suitable class (S1) is 3 ton/ha, while the productivity on the land is quite suitable (S2) of 1.61 ton/ha. (3) the results of the interview contained several points, namely the area of farmers land, the price of one durian fruit, pests/diseases that often attack plants. Keywords : Land Suitability, Productivity, Durian Plants